Using video presentation to recruit healthcare workers during COVID-19 pandemic - Binda, Filippo; Bisesti, Alberto; Pazzaglia, Silvia; Laquintana, Dario (Acta Biomedica Atenei Parmensis, 2020)
During COVID-19 pandemic, the recruitment of new personnel was necessary to guarantee an adequate healthcare level to all patients affected by SARS-CoV-2 virus. In order to deal with the sanitary emergency, unusual selection procedures have been adopted inside the public health system by searching for new healthcare personnel. The recruitment of new candidates with a short self-introduction was very effective and permitted to select 65 nurses.